النظام القانوني لخطاب الضمان المصرفي - يوسفي، نور الدين Yousefi, Nouruldin; كحلول، سامي (جامعة باتنة 1 الحاج لخضر - كلية الحقوق والعلوم السياسية, 2018)
The international trade movement resulted an urgent need to create new facilities in order to respond to this boom so banks took upon them selves the responsibility of providing their services according to what s appropriate to the international economic relation, and one of these banking services there is the guarantee letter which is considered as a commitments made by the commercial banks upon request of their clients in favour for a third party so called the beneficiary from the guaranty which is connected with the order by a contractual relationship to ensure that it was properly implemented and in order of protecting him from the clients poor implementation, the bank guarantee letter became the appropriate alternative to traditional credit facilities. The letters of bank guarantee took their placein the internal transaction over time due to the benifits achieved at he internal level which has spread in the internal despite the lack of legislation in this field.
نتج عن تسارع حركة التجارة العالمية الحاجة الماسة لوسائل ائتمانية جديدة تستجيب لهذه الطفرة، فأخدت البنوك على عاتقها تقديم خدماتها المصرفية بما يلائم العلاقات الاقتصادية الدولية، ومن بين هذه الخدمات خطابات الضمان المصرفية، التي تعد تعهدات تصدرها البنوك التجارية بناء على طلب عملائها لصالح طرف ثالث يسمى المستفيد من الضمان تربطه بالآمر علاقات تعاقدية يهدف لضمان تنفيذها على الوجه الأمثل، وكذا لحمايته من مخاطر سوء تنفيذ العميل لالتزاماته التعاقدية، فشكل خطاب الضمان المصرفي للمتعاملين البديل المناسب للوسائل الائتمانية التقليدية. وقد أخذت خطابات الضمان المصرفية مكانتها في المعاملات الداخلية مع مرور الوقت نظرا للفوائد التي حققتها على المستوى الدولي، فانتشر التعامل بها في إطار التجارة الداخلية برغم من النقص التشريعي في هذا المجال.
Keywords: الضمانات المصرفية -- الأنظمة القانونية -- الوسائل الائتمانية -- البنوك التجارية